Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/cxo.12814
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography and scleral contact lenses: clinical and research applications

Abstract: Anterior segment optical coherence tomography (OCT) provides a wealth of opportunities for modern contact lens practice. OCT imaging has numerous clinical and research applications related to the tear film, cornea, conjunctiva, sclera and ocular adnexae, in addition to soft, rigid, and hybrid contact lenses. This review summarises the potential use of OCT imaging in modern scleral contact lens practice including initial lens selection, assessing the scleral contact lens fit with respect to the cornea and scler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 98 publications
0
46
0
Order By: Relevance
“…Studies have shown that the curvature of the anterior sclera is significantly steeper temporally compared with nasally, with substantially less variation between the nasal, superior and inferior quadrants. 12,14,15 A steeper scleral curvature is associated with higher values of sagittal height (less elevated scleral surface), whereas the flatter curvature is associated with lower values of sagittal height (more elevated scleral surface). The scleral curvature varies with the ocular meridian examined, the distance from the limbus, age and so forth.…”
Section: Scleral Curvaturementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the curvature of the anterior sclera is significantly steeper temporally compared with nasally, with substantially less variation between the nasal, superior and inferior quadrants. 12,14,15 A steeper scleral curvature is associated with higher values of sagittal height (less elevated scleral surface), whereas the flatter curvature is associated with lower values of sagittal height (more elevated scleral surface). The scleral curvature varies with the ocular meridian examined, the distance from the limbus, age and so forth.…”
Section: Scleral Curvaturementioning
confidence: 99%
“…The scleral curvature varies with the ocular meridian examined, the distance from the limbus, age and so forth. 12 Despite the marked variations of the scleral curvature between ocular meridians and the distance from the limbus, many patients are successfully fitted with rotationally symmetric lens designs. 12…”
Section: Scleral Curvaturementioning
confidence: 99%
“…It can also provide useful information regarding scleral thickness, curvature, and toricity in addition to a detailed evaluation of the corneoscleral-limbal anatomy. 80 …”
Section: Scleral Lenses In Keratoconusmentioning
confidence: 99%
“…Intra‐operative use of AS‐OCT also enables dynamic corneal thickness measurements during the corneal collagen cross‐linking procedure, with the advantage that it is non‐invasive, rapid, and permits measurement at several corneal locations, in contrast to ultrasound pachymetry . As reviewed by Vincent et al, AS‐OCT also provides a wealth of information for the fitting of modern contact lenses, particularly mini‐scleral lens fittings.…”
Section: An Overview Of As‐oct Imaging In Humansmentioning
confidence: 99%